2008
DOI: 10.1038/modpathol.3801023
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling identifies p63 as a diagnostic marker for giant cell tumor of the bone

Abstract: Giant cell tumor of the bone (GCTOB) is a primary bone tumor that occurs mainly in young adults and is capable of locally aggressive growth. Its histologic appearance can resemble a number of benign and malignant tumors but no useful diagnostic marker is known currently. To identify diagnostic markers for this tumor, global gene expression profiling using cDNA microarray was performed on 6 fresh-frozen GCTOB, 3 aneurysmal bone cysts, 4 fibrous dysplasias and 12 giant cell tumors of tendon sheath/diffuse-type g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
54
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 21 publications
10
54
2
Order By: Relevance
“…When the number of CD147-positive cells was ≤5%, the tissue was considered negative; 6-25%, weak; 26-50%, moderate; and ≥51%, strong [16]. When the number of nuclei positively stained for p63 or mutant p53 was >10%, the tissue was considered positive, otherwise the tissue was considered negative [17]. …”
Section: Methodsmentioning
confidence: 99%
“…When the number of CD147-positive cells was ≤5%, the tissue was considered negative; 6-25%, weak; 26-50%, moderate; and ≥51%, strong [16]. When the number of nuclei positively stained for p63 or mutant p53 was >10%, the tissue was considered positive, otherwise the tissue was considered negative [17]. …”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] p63 immunostaining is also used to support a diagnosis of squamous cell carcinoma in various sites, including the head and neck, lung, 5 uterine cervix, and anus, 6 as well as metaplastic carcinoma of the breast, 7 urothelial carcinoma, sarcomatoid carcinoma, 8 and giant cell tumor of bone. 9,10 Recently, it was found that all p53 family members are involved in regulating muscle differentiation through the retinoblastoma (RB) protein.…”
mentioning
confidence: 99%
“…They can be locally aggressive and destructive with rapid growth leading to thinning and rupture of the cortical bone with invasion of adjacent soft tissues, but without invading and ulcerating the skin and subcutaneous tissue [3,4]. Generally, GCTBs most frequently occur in young adults between 20 and 40 years of age, with a slight predominance in females.…”
Section: Introductionmentioning
confidence: 98%
“…Generally, GCTBs most frequently occur in young adults between 20 and 40 years of age, with a slight predominance in females. They affect mainly the ends of long bones, and frequently occur in the distal end of the femur and the proximal end of the tibia [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%